Rates and predictors of general practitioner (GP) follow-up postdischarge from a tertiary hospital cardiology unit: a retrospective cohort study - Luke Y I Huang; Samuel J Fogarty; Arnold C T Ng; William Y S Wang (BMJ Open)
Objective Previous studies in cardiac patients noted that early patient follow-up with general practitioners (GPs) after hospital discharge was associated with reduced rates of hospital readmissions. We aimed to identify patient, clinical and hospital factors that may influence GP follow-up of patients discharged from a tertiary cardiology unit.Design Single centre retrospective cohort study.Setting Australian metropolitan tertiary hospital cardiology unit.Participants 1079 patients discharged from the hospital cardiology unit within 3 months from May to July 2016.Outcome measures GP follow-up rates (assessed by telephone communication with patients’ nominated GP practices), demographic, clinical and hospital factors predicting GP follow-up.Results We obtained GP follow-up data on 983 out of 1079 (91.1%) discharges in the study period. Overall, 7, 14 and 30-day GP follow rates were 50.3%, 66.5% and 79.1%, respectively. A number of patient, clinical and hospital factors were associated with early GP follow-up, including pacemaker and defibrillator implantation, older age and having never smoked. Documented recommendation for follow-up in discharge summary was the strongest predictor for 7-day follow-up (p<0.001).Conclusion After discharge from a cardiology admission, half of the patients followed up with their GP within 7 days and most patients followed up within 30 days. Patient and hospital factors were associated with GP follow-up rates. Identification of these factors may facilitate prospective interventions to improve early GP follow-up rates.